2015
DOI: 10.1063/1.4935238
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling irradiation induced grain growth with in situ transmission electron microscopy and coordinated modeling

Abstract: Nanostructuring has been proposed as a method to enhance radiation tolerance, but many metallic systems are rejected due to significant concerns regarding long term grain boundary and interface stability. This work utilized recent advancements in transmission electron microscopy (TEM) to quantitatively characterize the grain size, texture, and individual grain boundary character in a nanocrystalline gold model system before and after in situ TEM ion irradiation with 10 MeV Si. The initial experimental measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Due to the strong texture of the films, only the (111) peak exhibits a reasonable intensity, as shown in Fig. 9 Temperature-dependent grain growth, either thermally-induced or defect-stimulated, has been reported [41,[70][71][72][73][74][75][76][77][78]. Simulations reveal three grain-growth mechanisms, driven by grain rotation, curvature, and disorder [79][80][81][82], respectively.…”
Section: In-situ Tem Observation Of Structural Stability During Thermmentioning
confidence: 98%
“…Due to the strong texture of the films, only the (111) peak exhibits a reasonable intensity, as shown in Fig. 9 Temperature-dependent grain growth, either thermally-induced or defect-stimulated, has been reported [41,[70][71][72][73][74][75][76][77][78]. Simulations reveal three grain-growth mechanisms, driven by grain rotation, curvature, and disorder [79][80][81][82], respectively.…”
Section: In-situ Tem Observation Of Structural Stability During Thermmentioning
confidence: 98%
“…The decreasing density of the GBs is attributed to irradiation-induced grain growth. [32,33] From the 1D concentration profile across the GB, significant elemental redistribution is observed that indicates a peak distribution of Cr at the GB. The wavy distribution of Cr inside the columnar grains is also pronounced (Figure 4b5), the combination of the microstructural analysis inside the crystalline grains suggests that it may be induced by the compositional differences between the adjacent FCC and BCC phases.…”
Section: Doi: 101002/adma202002652mentioning
confidence: 99%
“…Recent development of advanced materials such as nanoporous [6,7], nanocrystalline (NC) [8][9][10][11][12], and nanocomposite materials [13,14] show promise for use as structural materials in extreme environments [9,10]. However, the grand challenge with broader applicability of such nanostructured materials has been the stability of the non-equilibrium microstructure during processing and deformation [15][16][17][18][19]. This significant degradation in properties of nanostructured materials is in part due to an increase in the large volume fraction of GBs along with TJs, which lack long-range crystalline order leading to diffusional processes such as sliding and/or rotation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Further, in nanostructured materials, such as NC metals, as the mean grain size decreases below 10 nm, the percent microstructure constituted by GBs and TJs increases and can be in excess of 50% [21,22]. Thus, due to the large volume fractions of non-equilibrium defects, NC metals exhibit altered physical responses to deformation, temperature, and radiation [15][16][17][18][19], i.e., the structural stability of NC materials is driven by GBs (planar defects), TJs (line defects), and their underlying structures [23,21]. Hence, a fundamental understanding of the relationship between the line/planar defect structures and the associated properties is highly relevant to develop stable, interface-dominant materials.…”
Section: Introductionmentioning
confidence: 99%